Study of Antibacterial Activity and Energy of Formation of Peptide Ligand Complexes With Hybrid Antibiotics Vancomycin-Azithromycin and Eremomycin-Azithromycin - E. E. Bykov; E. P. Mirchink; E. B. Isakova; E. N. Bychkova; E. N. Olsufyeva; A. N. Tevyashova (Антибиотики и Химиотерапия, 2020)
Antibacterial activity of hybrid antibiotics vancomycin-azithromycin (C11, C12-carbonate) and eremomycin-azitromycin (C11, C12-carbonate) was evaluated. Quantum chemical calculations of complexes of hybrid antibiotics with a model tripeptide ligand a, ε-di-Ac-L-Lys-D-Ala-D-Ala by the semi empirical PM6 method provided data on geometrical parameters of complexes along with the energy of their formation and the influence of protonation of the NHCH3 group. A correlation between the energy of formation of antibiotics-ligand complexes and antibacterial activity of hybrid antibiotics against Gram-positive bacterial strains was found.